La muerte en tránsito. Ficción y reconocimiento en Gran Sertón: Veredas de João Guimarães Rosa - Rowland, Clara (Verbum – Analecta Neolatina, 2012)
This essay explores the rhetoric of temporality in João Guimarães Rosa’s novel Grande Sertão: Veredas through the foregrounding of an element apparently alien to the oral culture that would seem to structure its universe: the letter as a figure of writing. Focusing on the episode of Nhorinhá’s delayed love letter to Riobaldo and on the implications of the ghostly temporality of epistolary communication, issues of representation, legibility, recognition and narrative will be discussed.